2008
DOI: 10.1093/humrep/dem327
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficiency, embryonic development and clinical outcome after the biopsy of one or two blastomeres for preimplantation genetic diagnosis

Abstract: While removal of two blastomeres decreases the likelihood of blastocyst formation, compared with removal of one blastomere, Day 3 in vitro developmental stage is a stronger predictor for Day 5 developmental potential than the removal of one or two cells. The biopsy of only one cell significantly lowers the efficiency of a PCR-based diagnosis, whereas the efficiency of the FISH PGD procedure remains similar whether one or two cells are removed. Delivery rates with live birth per started cycle were not significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(106 citation statements)
references
References 37 publications
5
96
1
4
Order By: Relevance
“…Furthermore, our data indicates that there is no significant difference in clinical outcomes following the removal of one versus two blastomeres. While these findings support previous data reported by Van de Velde et al [13] and Michiels et al [9], they are in contrast to studies performed by other groups [4,6]. The laboratory of Goossens et al [6] and De Vos et al [4] reported that the removal of more than one blastomere from a day 3 embryo has a detrimental affect on developmental potential and day 5 embryo quality, and subsequently on clinical outcomes.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Furthermore, our data indicates that there is no significant difference in clinical outcomes following the removal of one versus two blastomeres. While these findings support previous data reported by Van de Velde et al [13] and Michiels et al [9], they are in contrast to studies performed by other groups [4,6]. The laboratory of Goossens et al [6] and De Vos et al [4] reported that the removal of more than one blastomere from a day 3 embryo has a detrimental affect on developmental potential and day 5 embryo quality, and subsequently on clinical outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…Another area of difference between the current study and the studies performed by Goossens et al [6] and De Vos et al [4] was the embryo culture media that was used. We have previously shown that the type of embryo culture media used in the laboratory can have a significant impact on embryo development and clinical outcomes [2].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…PGD cannot detect abnormalities in all chromosomes and may also result in false-positive diagnoses. 41 Douma et al 35 found that 84% of 157 FAP patients of childbearing age (<40) reported PGD was not discussed in any clinical setting. Twenty percent indicated they would like more information on this technology.…”
Section: Discussionmentioning
confidence: 99%